2017
DOI: 10.1080/09670262.2017.1362591
|View full text |Cite
|
Sign up to set email alerts
|

Elainella gen. nov.: a new tropical cyanobacterium characterized using a complex genomic approach

Abstract: Cyanobacteria represent an ancient, monophyletic lineage of bacteria with the ability to undertake oxygenic photosynthesis. Although they possess a relatively high degree of morphological variability compared with other prokaryotes and there is a wealth of molecular data, there are still significant gaps in our knowledge of cyanobacterial diversity, especially in tropical areas. Here, we present a novel, filamentous, tropical cyanobacterium, which could be classified as Pseudophormidium based on morphological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 54 publications
1
24
0
2
Order By: Relevance
“…Likewise, there are four additional Oscillatoriaceae clades not related to Oscillatoria. Our phylogenies agree with those from Ishida et al [39], Jahodarová et al [11] and Nowicka-Krawczyk et al [13], which also shown the polyphyly of several Oscillatoriales families, including Microcoleaceae and Oscillatoriaceae. We highlight also that the family Pseudanabaenaceae (traditionally Synechococcales [31]) is not included in Oscillatoriales or Synechococcales clades, indicating that the phylogenetic position and taxonomy of this family must be revised, something already noticed by Mai et al [12].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Likewise, there are four additional Oscillatoriaceae clades not related to Oscillatoria. Our phylogenies agree with those from Ishida et al [39], Jahodarová et al [11] and Nowicka-Krawczyk et al [13], which also shown the polyphyly of several Oscillatoriales families, including Microcoleaceae and Oscillatoriaceae. We highlight also that the family Pseudanabaenaceae (traditionally Synechococcales [31]) is not included in Oscillatoriales or Synechococcales clades, indicating that the phylogenetic position and taxonomy of this family must be revised, something already noticed by Mai et al [12].…”
Section: Discussionsupporting
confidence: 91%
“…The growing number of new taxa descriptions, the availability of 16S rRNA gene sequences for type species, and the access to powerful computational tools [10], has brought to light that many cyanobacterial families from the classical, morphological-based taxonomy are polyphyletic, warranting taxonomical revisions [11–13]. Up to now, the only revision at the order level for Cyanobacteria, on the basis of robust phylogenetic analysis and morphological descriptions, concerned the Synechococcales and was carried out by Mai et al .…”
Section: Introductionmentioning
confidence: 99%
“…The Synechococcales contains a great number of molecularly and morphologically divergent taxa. Seventy-four genera were recognized in the order in the newest taxonomic system (Komárek et al 2014), with (counting Lagosinema) 18 additional genera being published since that treatment (Dvořák et al 2015;Song et al 2015;Vaz et al 2015;Li & Li 2016;Miscoe et al 2016;Sciuto & Moro 2016;Dvořak et al 2017;Jahodářová et al 2017aJahodářová et al , 2017bSciuto et al 2017;Mai et al 2018). Furthermore, there are numerous unnamed or incorrectly named sequenced species that appear in our Science for the Developing World (OWSD) and the Swedish International Development Cooperation Agency (Sida) postgraduate training fellowship to Sandra C. Akagha (Grant No.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the decreasing price of whole genome sequencing (WGS) has made it more accessible and allowed for its use in phylogeny 21 . WGS can resolve much finer patterns of diversity at and below the species level For example, WGS has been employed to describe the tropical cyanobacteria Ellainela 22 and Moorena 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%